MEMBANGUN DAYA SAING PERGURUAN TINGGI SWASTA MELALUI MARKETING MIX: KAJIAN EMPIRIS PADA UNIVERSITAS LANCANG KUNING - Ahmad Ade Irwanda; Wentisasrapita Abiyus; Richa Afriana Munthe (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to evaluate how the marketing mix elements (7Ps) influence prospective students' decision to choose Lancang Kuning University. The analysis focuses on seven main dimensions: Product (study program quality), Price (tuition fees), Place (campus location), Promotion (promotional efforts), People (quality of lecturers and administration), Process (learning procedures), and Physical Evidence (infrastructure facilities). Quantitative methods are used in this research study by collecting data through questionnaires distributed to 192 new students at the Faculty of Economics and Business (FEB). This resulted in data being tested using a variety of statistical tests, including validity tests, reliability tests, classical assumption testing, multiple linear regression, and testing with the F-test and T-test using SPSS software. The results show that overall the seven dimensions have a significant influence simultaneously (Adjusted R² = 62.5%). However, partial analysis reveals that only Price, Promotion, and Process have significance. The main determinants include affordable tuition fees, effective promotion, and simple administrative processes. This research contributes to the development of marketing strategies for private universities in Indonesia by emphasizing the importance of prioritizing the aspects of cost, targeted promotion, and efficiency of academic processes to strengthen the competitiveness of the institution.  Keyword: marketing mix; higher education; student decision making Abstrak: Penelitian ini bertujuan untuk mengevaluasi bagaimana elemen-elemen marketing mix (7P) memengaruhi keputusan calon mahasiswa dalam memilih Universitas Lancang Kuning. Analisis berfokus pada tujuh dimensi utama: Produk (kualitas program studi), Harga (biaya kuliah), Tempat (letak kampus), Promosi (upaya promosi), Orang (kualitas dosen dan tata usaha), Proses (prosedur pembelajaran), dan Bukti Fisik (sarana prasarana). Metode kuantitatif digunakan pada kajian riset ini dengan mengumpulkan data melalui angket yang dibagikan pada 192 mahasiswa baru di Fakultas Ekonomi dan Bisnis (FEB). Sehingga diperoleh data yang diuji menggunakan beragam uji statistik, termasuk uji validitas, uji reliabilitas, pengujian asumsi klasik, regresi linier berganda, serta pengujian dengan uji F dan uji T menggunakan perangkat lunak SPSS. Hasil menunjukkan bahwa secara keseluruhan ketujuh dimensi tersebut memiliki pengaruh signifikan secara simultan (Adjusted R² = 62,5%). Namun, analisis parsial mengungkapkan bahwa hanya Price, Promotion, dan Process yang memiliki signifikansi. Faktor penentu utama meliputi biaya pendidikan yang terjangkau, promosi yang efektif, dan proses administrasi yang sederhana. Penelitian ini berkontribusi terhadap penyusunan strategi pemasaran untuk kampus swasta di Indonesia dengan menekankan pentingnya prioritas pada aspek biaya, promosi yang terarah, serta efisiensi proses akademik untuk memperkuat daya saing institusi. Kata kunci: marketing mix; pendidikan tinggi; keputusan mahasiswa;